Public Policy and Methodological Myopia - Marcos Giansante (Mises)
The 2023 systematic review published by the Cochrane Library on the use of physical barriers to contain respiratory viruses became a landmark in the scientific and political debate surrounding non-pharmaceutical interventions during pandemics. This article analyzes the content and implications of the Cochrane Library (2023) study through the lens of Austrian epistemology, highlighting the limits of empirical knowledge in complex social phenomena, the risks of scientistic pretension in public policy formulation, and the dangers of state coercion when based on uncertain evidence. It concludes that institutional prudence and respect for individual liberty must prevail in the face of scientific uncertainty.